Importance of Interleukin-10 in Genetic Susceptibility of Mice to Coccidioides immitis - Fierer, Joshua (American Society for Microbiology (ASM), 1998)
Inbred strains of mice vary in their susceptibility to Coccidioides immitis. We infected resistant DBA/2 (D2) mice and three susceptible strains of mice (C57BL/6 [B6], BALB/c, and CAST/Ei) by intraperitoneal injection of arthroconidia and determined the severity of infection based on colony counts of fungus in the spleens and lungs 14 days after infection. We used quantitative reverse transcription-PCR to measure the amounts of cytokines made in the spleens and lungs of infected mice. Susceptible mice made 1,000-fold more interleukin-10 (IL-10) than resistant D2 mice and about 10-fold more IL-4. In contrast, D2 mice had more IL-12 p40 in their lungs than did B6 mice. Resistant and susceptible mice made equivalent amounts of gamma interferon, IL-6, and IL-2. In order to determine whether IL-10 adversely affected the response to C. immitis, we infected IL-10-deficient mice, and they were found to be as resistant as D2 mice. This result indicates that IL-10 plays a crucial role in determining susceptibility to C. immitis in inbred mice. Because IL-4 mRNA levels were higher in most strains of susceptible mice, we also infected IL-4-deficient B6 mice. They were more resistant than B6 controls but not as resistant as IL-10-deficient mice. Thus, both IL-10 and IL-4 adversely affect the ability of C57BL mice to resist infection with C. immitis, but IL-10 has a larger effect and is the cytokine that is consistently associated with susceptibility in all strains of inbred mice.